A multiplex pneumonia panel for diagnosis of hospital-acquired and ventilator-associated pneumonia in the era of emerging antimicrobial resistance - Jitmuang A. (2023)
Background: Antimicrobial resistance (AMR), including multidrug (MDR) and extensively drug-resistant (XDR) bacteria, is an essential consideration in the prevention and management of hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP). In the AMR era, the clinical utility of the BioFire FilmArray Pneumonia Panel Plus (BFPP) to diagnose HAP/VAP has not been thoroughly evaluated. Methods: We enrolled adult hospitalized patients with HAP or VAP at Siriraj Hospital and Saraburi Hospital from July 2019–October 2021. Respiratory samples were collected for standard microbiological assays, antimicrobial susceptibility testing (AST), and the BFPP analysis. Results: Of 40 subjects, 21 were men. The median duration of HAP/VAP diagnoses was 10.5 (5, 21.5) days, and 36 endotracheal aspirate and 4 sputum samples were collected. Standard cultures isolated 54 organisms—A. baumannii (37.0%), P. aeruginosa (29.6%), and S. maltophilia (16.7%). 68.6% of Gram Negatives showed an MDR or XDR profile. BFPP detected 77 bacterial targets—A. baumannii 32.5%, P. aeruginosa 26.3%, and K. pneumoniae 17.5%. Of 28 detected AMR gene targets, CTX-M (42.5%), OXA-48-like (25%), and NDM (14.3%) were the most common. Compared with standard testing, the BFPP had an overall sensitivity of 98% (88-100%), specificity of 81% (74-87%), positive predictive value of 60% (47-71%), negative predictive value of 99% (96-100%), and kappa (κ) coefficient of 0.64 (0.53-0.75). The concordance between phenotypic AST and detected AMR genes in Enterobacterales was 0.57. There was no concordance among A. baumannii, P. aeruginosa, and S. aureus Conclusions: The BFPP has excellent diagnostic sensitivity to detect HAP/VAP etiology. The absence of S. maltophilia and discordance of AMR gene results limit the test performance.